ETHNOMEDICINAL PLANTS USED BY TRIBAL COMMUNITIES FOR THE TREATMENT OF VARIOUS DISEASES IN BHADRACHALAM AND CHARLA AREA OF KHAMMAM DISTRICT, TELANGANA STATE - Ghani, Md.; Suresh, V.; Raju, S.; Mustafa, Md. (International Journal of Ayurveda and Pharma Research, 2015)
Ethnobotanical field work is different from the routine field collection, which are done usually by taxonomists or flora writers. While taxonomist give emphasis on plants and their habitat, the ethnobotanists, in addition to these aspect, record the relationship of these plants with the local inhabitants. Therefore, the first step in ethnobotanical field work is to identify the local inhabitants or primitive societies and their regional jurisdiction. Field study in a tribal area gives first hand information. Here the ethanobotanist apart from collection of plant, also discuses and records the uses of plants with the help of informants. Great patience and perseverance are required in ethnobotanical study. Traditionally used medicinal plants have been a source of relief in controlling various types of diseases throughout the globe. Tribal people have traditional knowledge of plant species use for different purposes such as food, colors, gums, medicine etc. Present study deals with ethnobotanical study to explore about ethnomedicinal plants using for curing various diseases. We have conducted an ethnobotanical survey to collect the information about the traditional medicinal plants for various diseases by the tribes of Bhadrachalam and Charla area of Khammam district. In our investigation we have recognized 25 taxa, belonging to 23 genera of 17 families of magnoliphyta are used for different diseases. These collected plants were planted in our research field for further studies. Different explants of these plants have been used for plant tissue culture studies like micropropagation and conservation of germplasm. The herbal plants, fruits, seeds are preserved and documented in the form of herbarium and specimens.